REFINERY STAGE OF OXIDES RESTORATION IN ROTATIONAL FURNACES - S. L. Rovin; L. E. Rovin; T. M. Zayats; N. G. Kislitsyna (Литьë и металлургия, 2012)
The article is devoted to research of process of the iron-containing waste recycling in rotary tilting furnaces, in particular, to the phenomenon of formation of ball iron at transition from hard-phase to liquid-phase stage of iron restoration from scale.